Community energy balancing - Coutinho, C.; Rodrigues, R.; Silva, M. (Swarm intelligence application for the cities of the future, 2025)
This chapter informs the reader about intelligent swarms, describing a use case for swarm development focused on energy balancing within an energy community. It details the energy and communication exchanges, the proposed actors within the community, and the two-stage approach, which encompasses six scenarios to be considered. This concept follows a multi-layer edge-fog-cloud approach to facilitate the creation of energy communities, enable intra/inter-community communication, address low-voltage grid capillarity, and provide grid monitoring and node orchestration. Ultimately, it aims to improve efficiency, balance grid nodes, and increase the share of renewable energy sources. This chapter describes the approach taken in the European project TaRDIS towards supporting the development of swarm projects in these scenarios.